PERANAN PEMERINTAH KABUPATEN ROKAN HULU DALAM PENGELOLAAN OBJEK WISATA RUMAH BATU SEROMBOU DI DESA SEROMBOU INDAH KECAMATAN RAMBAH HILIR - Wardana, Data; Al Hafis, Raden Imam (UIR PRESS, 2018)
The development of the world of tourism in Indonesia is very promising, the government both at the level of central and regional make the tourism sector as a superior sector that must be developed to increase the national income and regional income. Rokan Hulu regency is one of the existing regencies in Riau Province that has a tourist destination among religious tourism Rokan Hulu Great Mosque, Tuanku Tambusai Fortress which is a historical and nature tourism. One of the natural attractions is Serombou stone house located in the village Serombou Indah District Rambah Hilir. But the condition of the sights are not maintained and indicated neglected from development activities. In addition, inadequate access to transportation and road access make it less visited than the National Day. Therefore, this research is conducted to know how the role of Rokan Hulu District Government in Management of Serombou House Tourist Attraction. What is the type of research is descriptive cultivation study with informants Head of Tourism Office Rokan Hulu District, Village Head, BPD Serombou Beautiful village, Head of Hamlet and Community Leaders. From the result of the research, it can be concluded that the regency of Rokan Hulu regency in the management of tourist destinations, tourism promotion and the increase of public participation in tourism management of Batu Serombou house has less role. It is seen that the management of attractions Serombou stone house new limited discourse and not contained in the program and government activities.